Effectiveness of Cooling Methods in Reducing Losses During Cherry Storage (Agricultural Engineering, 2024)
Efficient use of energy and resources is vital for fostering the sustainable development of our planet and fighting hidden hunger. One way to address this issue is by preserving the quality of raw materials from fruits over a prolonged period. However, fruits have the highest rate of losses and waste among food products. Incorrect selection of cooling procedures and inappropriate cooling rates can lead to post-harvest quality losses, which in turn will result in loss of product quality and energy. Research into methods capable of minimizing losses and extending the storage life of fruits is essential to determine their effectiveness. The purpose of the research was to evaluate the impact of different cooling methods on the reduction of losses and the extension of the shelf life of cherries. The study involved sweet cherries of different ripening periods (Melitopolska chorna, Krupnoplidna and Valerii Chkalov) and sweet cherries of the Vstriecha variety. The influence of room cooling, forced air cooling, hydrocooling with the addition of lactic and acetic acid, and combined cooling method on cooling rate, weight loss, epiphytic microflora condition, respiratory intensity and heat generation during cherry storage was analyzed. The highest fruit weight losses were observed when using the forced air cooling method, ranging from 1.76 to 1.96%. The combined cooling method for cherries and sour cherries reduced average fruit weight losses by 11.3-22.9 times compared to other methods. When using the combined method, the number of bacteria and fungi on the surface of cherry fruits remained at the same level as before cooling or decreased by 10 to 40% depending on the variety. On the surface of the fruits of the Vstriecha sour cherry variety, the number of bacteria and fungi decreased from 20 to 60% compared to the indicators of the epiphytic microflora before cooling. The proposed combined precooling method is determined to be the most effective in terms of technological indicators and preservation of the quality of cherry and sour cherry fruits. Further studies of the impact of cooling methods on cherry quality will allow the development of mathematical modeling approaches to quantitatively describe precooling processes throughout the entire refrigeration chain for fruit preservation.